STABILISASI TANAH LEMPUNG MENGGUNAKAN CAMPURAN ABU SEKAM PADI DAN KAPUR DIEVALUASI DARI NILAI CBR UNSOAKED - Sajati, Anis Fajar; Wulandari, Sri (Direktorat Bina Teknik Jalan dan Jembatan, 2020)
The quality of original soil in the Hambalang area of Citeureup - Bogor, virtualy shows low density mainly the unsoaked CBR value therefore unusable for subgrade stucture, and can cause road construction to be easily damaged. Soil stabilization conducted in this research is chemical stabilization using the selected mixture was rice husk ash (ASP) and lime. This test carried out with clayey by adding a mixture of rice husk ash and lime in a variation of clayey weight percentage of 0%, 4%, 8% and 12% of the dry weight of the soil, where the ratio between lime and rice husk ash is 50%: 50% and each mixture made as many as 3 samples. Water content in the original soil was 75.2 % decreased to 49.5% at 12% variation. The mixture of rice husk ash and lime ash makes the value of the liquid limit (LL), plastic limit (PL), and shrinkage limit (SL) decrease. This shows that the effect of rice husk ash and lime as added material in soil improvement has changed the technical properties of expansive clay for the better. CBR soil test increases significantly. CBR in the original soil of 1.9% increased to 8.0% in the rice ash husk plus lime mixture 4%, then experienced a significant increase in the 8% rice ash husk plus lime mixture that is 30.1%, and in the rice ash husk plus lime mixture 12% decreased to 10.7%. it can be concluded that the optimum undistrube CBR obtained at mixing with a percentage of 8% is 30.1%.Keywords: Stabilization, road, clay soil, mixture, optimum, CBR